Pendidikan Spiritualitas yang Berbasis Ekologis sebaga Upaya Menumbuhkan Kesadaran Lingkungan - Raisul Muhadidsin; Nabila Firliya Zahra; Hafidz Taqiyuddin (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
The global ecological crisis indicates that technical methods and regulations alone are insufficient to change human behavior related to the environment, thus requiring approaches that touch on moral and spiritual aspects. This study aims to design and examine spiritual-ecological education as an alternative approach in building sustainable environmental awareness. This research uses a qualitative method based on literature study using Miles and Huberman's analysis through summarization, exposition, and data conclusion drawing. The results of the study show that spiritual-ecological education has three important outcomes, namely: (1) the integration of the values of monotheism, khalifah, and ecological trust creates a solid environmental ethical framework; (2) the methods of ecosufism and scientia sacra deepen students' affective and reflective understanding of the relationship between humans and nature; and (3) contextual learning methods such as eco-pesantren and environmental programs may connect spiritual values with real ecological activities. This study contributes scientifically by developing a theoretical basis for spiritual-ecological education that combines theological, philosophical, and pedagogical aspects of environmental education. These results imply the importance of developing lesson plans and teacher training that place spirituality as the basis of ecological understanding, with the caveat that drawing general conclusions from the study results requires further empirical testing.